The effect of dietary energy content and the provision of a β-adrenergic agonist in the diet, on the production and meat quality of South African Mutton Merino feedlot lambs - Genis, Maria Petronella (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScAgric)--Stellenbosch University, 2014.